Ukrainian SSR police activities in combating crime in the late 1950s - V. A. Grechenko (Law and Safety)
The main aspects of the activity of the police of the Ukrainian SSR related to the fighting against crime in the late 1950s have been studied. Historiography of this problem is virtually absent, Ukrainian scholars, historians of law, have not directly studied this topic and period. The essence of the criminal law policy of the state in the first years of de-Stalinization has been highlighted. Since the mid-1950s, legislative activity in Ukraine has become more intense, the number of new regulations has increased rapidly, and their quality has improved. The death penalty – execution by firing squad - was declared an exceptional measure of punishment. Its application was allowed only for the most serious and dangerous for the state crimes specified in the law. The maximum term of imprisonment has sharply decreased from 25 to 15 years. Statistics on the general state of criminal crime in this period are given. Forms and methods in combating crime management by the Ministry of Internal Affairs of the Republic are analyzed, in particular the content and direction of directives and orientations of the Ministry of Internal Affairs, their differences, features of inspections of operational and service activities of individual police departments of the regions with further consideration of its results at the board of the Ministry of Internal Affairs and the importance of all these measures in improving the work of local police. The state of crime in certain areas and indicated measures to improve the work of local police in this area are analyzed in the directives. Orientations in their structure and content were slightly less administrative than directives, as they were not signed by the Minister of the Interior, but by the Deputy Minister of Police and at the same time the Head of the Police Department of the Ministry of Internal Affairs of the Ukrainian SSR or one of the Interior Ministry departments. They also had a little more specificity on examples of crimes.